Effectiveness, Safety, and Costs of Thromboprophylaxis with Enoxaparin or Unfractionated Heparin Among Medical Inpatients With Chronic Obstructive Pulmonary Disease or Heart Failure - Alpesh N. Amin; Alex Kartashov; Wilson Ngai; Kevin Steele; Ning Rosenthal (Journal of Health Economics and Outcomes Research)
**Background:** Chronic obstructive pulmonary disease (COPD) and heart failure (HF) are risk factors for venous thromboembolism (VTE). Enoxaparin and unfractionated heparin (UFH) help prevent hospital-associated VTE, but few studies have compared them in COPD or HF.